Pengembangan Pembelajaran Sejarah Berbasis Microsoft Teams Untuk Membentuk Kecakapan Abad 21 - Asyif Awaludin Romadhoni; Supardi Supardi; Aman Aman (Universitas Muhammadiyah Prof. Dr. Hamka, 2021)
The Covid-19 pandemic has changed all aspects of human life. One of them is education. The government has launched a Learning From Home (BDR) policy to tackle the spread of COVID-19. This has an impact on the learning process and inculcating character values ​​among the younger generation. History learning certainly plays an important role in shaping the character of the younger generation and becomes one of the solutions to moral decadence during the pandemic. Therefore, history learning needs to be arranged creatively by innovating learning technology, one of which is Microsoft Teams. This article aims to describe a Microsoft Teams-based history learning model by incorporating learning technologies such as broadcast. This article is written with descriptive writing method. The theories used to analyze and develop this learning model include the concepts of understanding, feeling, acting, and the example of Ki Hadjar Dewantara; the Smart School and Good School concepts developed by Matthew Davidson, Thomas Lickona, and Vladimir Khmelkov; and the concept of Teaching Controversial Issues based on Thomas Lickona's research. The history learning model based on Microsoft Teams consists of several stages, namely Preparation of Learning Implementation Plans (RPP); Material Ray Making; Asynchronous Learning by sharing podcasts of material into Teams Classes; Synchronous Learning Discussing Rays; Synchronous Learning that Discusses the Perspective of Characters, Historical Actors, or Experts and Discusses; and Control of Character Guidance with Homeroom and Counseling Teachers. This model can be applied in history learning in an effort to inculcate character values ​​and competencies in the 21st century by inviting students to continue to plan and realize good plans for the better.